Analysis of Factors Affecting Local Household Income Derived from Eucalyptus Woodlot in Jamma District, Ethiopia - Tesfanesh Ababu Kebede (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
A woodlot is a piece of woodland that is a privately owned farm for tree plantation. It has become a common activity among local households in Ethiopia. Currently, local households in Jamma District, Ethiopia predominantly plant eucalyptus woodlot as their alternative income source. However, there is no empirical evidence on the factors that affect driving maximum income from Eucalyptus woodlot. This study investigated the factors affecting income from Eucalyptus woodlots in the Jamma district. Data were collected and organized by the household survey, key informant interview, field observation, and focus group discussion. Qualitative and quantitative data were used from primary and secondary sources. A total of 150 randomly selected households were interviewed from Eucalyptus woodlot owners. Multiple linear regression analysis was applied to determine the significant variables affecting the income amount derived from eucalyptus woodlot. The results described the socioeconomic characteristics of households, and investigate the determinants of Eucalyptus woodlot income level. Age, family size, distance from the market, and household experience are the major factors that determine the income of households derived from Eucalyptus woodlot production. Household income derived from eucalyptus woodlot was negatively and significantly affected by the distance where their woodland was located from the market and their experience in planting Eucalyptus as the regression analysis showed. The result of this study suggests that technical manuals should be implemented to minimize its negative impacts on the environment to made the households better benefited from their Eucalyptus woodlot products and for sustainable production.